DAMPAK PERKEMBANGAN REVOLUSI INDUSTRI 4.0 TERHADAP SUMBER DAYA MANUSIA INDUSTRI RETAIL: STUDI PADA PENGELOLA GEDUNG SUN PLAZA MEDAN - Lintong, Elisabeth Marlina Sari; Ferawaty, Ferawaty (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2024)
The company’s human resources must be able to evolve to become more productive, innovative, and adaptive in every generation. This is necessary to ensure that human resources are competitive in the current era of Industry 4.0. Business processes and the company’s human resources are now influenced by the new technologies they use. Currently, the standards and qualifications of human resources need to be improved. The management of Sun Plaza Medan Shopping Center also experiences this challenge. Therefore, the aim of this study is to understand and analyze how management will address the growth of Industry 4.0. Additionally, this research will examine the impact of Industry 4.0 on human resource development. The study will also explore how management can improve the qualifications required by the management of Sun Plaza Medan Shopping Center. This research employs two approaches: descriptive qualitative and quantitative. The qualitative descriptive results are derived from interviews and observations at Sun Plaza Medan. The quantitative results come from surveys conducted with employees of the management of Sun Plaza Medan Shopping Center. The research findings from interviews and questionnaires indicate that Sun Plaza Medan Shopping Center still requires human resources to operate, as it is a shopping center that prioritizes services to visitors. The staff currently working at Sun Plaza Medan Shopping Center meet the required qualifications. The survey results reveal that they are interested in the developments of Industry 4.0 and have the desire to learn and understand the advancements in Industry 4.0.